Cognitive Engagement Mediates the Relationship between Positive Life Events and Positive Emotionality - Strobel, Alexander; Anacker, Kristin; Strobel, Anja (Frontiers in Psychology, 2017)
Need for Cognition (NFC) is conceptualized as an individuals’ tendency to engage in and enjoy effortful cognitive activity and, thus, captures one’s cognitive engagement. It plays a well-established role in information processing in experimental or academic contexts. However, so far comparably little is known about its consequences for other than purely cognitive or academic outcomes. Indeed, NFC is positively associated with personality traits pertaining to Positive Emotionality (PE) and negatively to traits related to Negative Emotionality (NE). Moreover, evidence suggests NFC to be related to an active, problem-focused coping style. We therefore hypothesized NFC to mediate between life events and individual differences in PE and NE. In a sample of N = 202 volunteers from the general population, we observed that the number of past positive and negative life events had direct effects on PE, and NE, respectively, and that for positive life events, a mediating effect on PE via NFC was observed, with a higher number of past positive life events being related to higher NFC that in turn was related to increased PE. Thus, the present results lend support to the notion of NFC as an important factor supporting personal well-being by way of its mediating role between the number of past positive life events and positive affect.